Cases on audio-visual media in language education - Xiang, Catherine Hua (Advances in educational technologies and instructional design (AETID) bokk series, 2018)
"This book shares good practices in the field of using audio-visual media and inspire more teachers and learners take full advantage of technology and enable effective learning both inside and beyond the classrooms. Building on theory and research, it offers practical ideas and methodologies so that the readers could easily borrow and apply in their own contexts"...